PENGGUNAAN MEDIA TRANSPARANSI OHP SEBAGAI ALAT BANTU INSTRUKSIONAL PENGAJARAN IPA DENGAN PENDEKATAN KETRAMPILAN PROSES SEBAGAI UPAYA UNTUK PENINGKATKAN KUALITAS PENDIDIKAN IPA (THE USE OF OHP AS AN INSTRUCTIONAL MEDIA ON SCIENTIFIC TEACHING AND LEARNING SUPPORTED BY SKILL- PROCCESSES APPROACH TO RAISE THE QUALITY OF SCIENTIFIC EDUCATION) - AHMAD FAUZI (Bioedukasi: Jurnal Pendidikan Biologi, 2006)
The aims of this research are to find out: (1 ) the influence of using the OHP media and LKS (Lembar Kerja Siswa/student worksheet) to raise the quality of scientific education (2) the influence using demonstration method and information discussion method to raise the quality of scientific subject education (3) interaction of factor 1 and factor 2 in raising the quality of scientific education.The research used the experiment method with 2X2 factorial design. The researcher collected the data by giving test to the subject. The population of the research was the third grade of senior high school (MTsN) Salatiga, the number of the samples were 80 students (divided into two classes), taken from sub-populations of 268 students (in six classes). The researcher applied random sampling technique. The data was analyzed by using ANOVA at the level of significance (X = 0,05.The results showed that: ( 1 ) there is a significant difference of using the OHP and LKS in rising the quality of scientific subject education (2) there is significant difference of using the demonstration method and information discussion method in rising the quality of scientific subject education (3) there is no interaction between the usage of OHP transparence and LKS with the usage of demonstration and information discussion method to raise the quality of scientific education.